2018
DOI: 10.1016/j.ygcen.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Early embryonic modification of maternal hormones differs systematically among embryos of different laying order: A study in birds

Abstract: Vertebrate embryos are exposed to maternal hormones that can profoundly affect their later phenotype. Although it is known that the embryo can metabolize these maternal hormones, the metabolic outcomes, their quantitative dynamics and timing are poorly understood. Moreover, it is unknown whether embryos can adjust their metabolic activity to, for example, hormones or other maternal signals. We studied the dynamics of maternal steroids in fertilized and unfertilized rock pigeon eggs during early incubation. Emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 57 publications
1
40
0
Order By: Relevance
“…Since the decline of androgen concentrations was found throughout the egg, it cannot be due to dilution with albumen or water, or embryonic uptake. This indicates that the maternal T and A4 are metabolized by embryonic and/or maternal enzymes, which is in line with the suggestions made in other studies (Gilbert et al, 2007;Kumar et al, 2018a;Parsons, 1970;Vassallo et al, 2014), as explained below. This raises the intriguing question as to which metabolic products these androgens are converted into, as this will determine the biological significance of maternal hormone deposition.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Since the decline of androgen concentrations was found throughout the egg, it cannot be due to dilution with albumen or water, or embryonic uptake. This indicates that the maternal T and A4 are metabolized by embryonic and/or maternal enzymes, which is in line with the suggestions made in other studies (Gilbert et al, 2007;Kumar et al, 2018a;Parsons, 1970;Vassallo et al, 2014), as explained below. This raises the intriguing question as to which metabolic products these androgens are converted into, as this will determine the biological significance of maternal hormone deposition.…”
Section: Discussionsupporting
confidence: 91%
“…2) at such an early stage of embryonic development as aromatase is expressed only after day 5 of incubation in chicken (Nomura et al, 1999), which is also experimentally supported by the lack of such early androgen conversion to estrogens (Parsons, 1970). Parsons (1970) suggested 5β-androstane-3α,17β-diol as the main metabolite in an in vitro study on metabolism of radiolabelled T by the 2-dayold chicken embryo; suggested conjugated etiocholanolone as the main metabolite in the yolk albumen homogenates of European starling eggs incubated for 6 days; and Kumar et al (2018a) showed etiocholanolone and its conjugate as main androgenic metabolites in rock pigeon eggs incubated for 4.5 days. These studies indicate a 5β-reduction, followed by 3α-hydroxylation metabolic route for maternal T and A4 (Fig.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although the machinery is thus in place to perceive maternal hormonal cues, there is also growing evidence that embryos rapidly and heavily metabolize maternal hormones in the egg [62,78,79]. Intriguingly, most of these metabolites are (supposedly) inactive forms of the free steroids, such as conjugated forms or etiocholanolone in the case of androgens [80].…”
Section: (A) Conflicts Between Mothers and Their Offspringmentioning
confidence: 99%
“…Furthermore, variation in maternal corticosterone may not be reflected in embryos if mothers regulate corticosterone deposition into eggs or if embryos metabolize maternal hormones (Moore and Johnston 2008;Paitz et al 2012), both of which may be more true for natural than experimental levels of corticosterone. Recent studies on reptiles and birds have shown that hormones such as estradiol and testosterone are metabolized early in development and that embryonic uptake of metabolites occurs much later (Paitz et al 2012;Kumar et al 2018Kumar et al , 2019. This, coupled with the possibility that embryos may actively control their endocrine environment, suggests that embryos can be buffered from the effects of maternal corticosterone Kumar et al 2018Kumar et al , 2019.…”
Section: Discussionmentioning
confidence: 99%